Treatment of rat nephrotoxic nephritis. Use of 5-fluorouracil or methotrexate-5-fluorouracil association - Almeida, D. B. de; Curi, P. R. (My University, 1984)
To evaluate the effect of 5-fluorouracil (F) and methotrexate-5-fluorouracil association (MTX-F) on nephrotoxic nephritis, seven groups of 10 rats were inoculated with anti-rat glomerular basement membrane serum (AGBMS); five groups were treated with different doses of F, beginning on the 2nd or the 6th day, one group with MTX-F beginning on the 2nd day and one group (control) with distilled water. Twenty-four hour proteinuria was determined weekly until the 71st day. The kidneys were examined histologically and by immunofluorescence. The group treated with F (1.3 mg/100 g body weight) developed a severe glomerulonephritis similar to the control group; (b) the groups treated with F (2.0 mg/100 g body weight) or with MTX-F showed progressively lower proteinuria, less severe histological changes and less intense fluorescence due to autologous antibodies. The best results were observed in the MTX-F group and in the F group treated from the 6th day. These groups presented at the 71st day proteinuria of 84 and 91 mg as compared to 312 mg in the control group, and minimal histological lesions as compared to glomerulosclerosis and tubular atrophy in the control group. We concluded that either F or MTX-F produced significant improvement of nephrotoxic nephritis due to inhibition of autologous antibody production.
Keywords: fluorouracil; glomerulus basement membrane antibody; methotrexate; animal model; antibody production; drug therapy; immune complex nephritis; kidney; methotrexate 5 fluorouracil; nonhuman; proteinuria; rat; therapy; Animal; Drug Therapy, Combination; Fluorescent Antibody Technique; Fluorouracil; Glomerulonephritis; Kidney; Kidney Function Tests; Male; Methotrexate; Rats; Rats, Inbred Strains